Pandemic Vulnerability Mapping in East Java and Its Connection to Local Economic Resistance - Rizky Zulkarnain; Karuniawati Dewi Ramadani (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
The objectives of this study are to measuring and to mapping pandemic vulnerability in East Java as well as to examine the association between pandemic vulnerability and local economic resistance. To achieve the objectives, this study employs several techniques: descriptive analysis, principal component analysis, cluster analysis, and analysis of variance. The data were acquired from various sources, that cover health, social, economic, and environmental conditions. The results showed that there were seven most vulnerable districts in East Java. They were Kota Surabaya, Kabupaten Sidoarjo, Kabupaten Gresik, Kota Kediri, Kota Malang, Kota Mojokerto and Kota Madiun. The core pandemic indicators were population mobility, the number of COVID-19 cases and its mortality, population density, air pollution, the prevalence of diabetes, and the share of secondary and tertiary sectors. Furthermore, this study found that there were negative association between pandemic vulnerability and local economic resistance in East Java.